2019
DOI: 10.3390/geosciences9080341
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Effect of Wet-Dry Cycles and Rainfall on Highway Slope Made of Yazoo Clay

Abstract: Expansive Yazoo clay soil is susceptible to volumetric deformation and is dominant in central Mississippi and other neighboring southern states of the United States. Recurring shrink-swell behavior causes a significant problem to infrastructures in the area. Although Yazoo clay causes a significant problem in the deep southern states, limited study has been conducted on the behavior of Yazoo clay, especially in the presence of rainfall. The objective of this current study is to investigate the coupled effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…The effect of plant roots on slope stability can be divided into hydrological and mechanical factors, which can be valuable to ensure slope stability [1,2,5,21,[25][26][27][28][29][30][31][32][33][34][35][36][37]. With regards to the hydrological effects, plants intercept rainfall allowing it to slowly infiltrate into the soil by reducing the runoff velocity and, thus, reduces soil erosion [7,8,38].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of plant roots on slope stability can be divided into hydrological and mechanical factors, which can be valuable to ensure slope stability [1,2,5,21,[25][26][27][28][29][30][31][32][33][34][35][36][37]. With regards to the hydrological effects, plants intercept rainfall allowing it to slowly infiltrate into the soil by reducing the runoff velocity and, thus, reduces soil erosion [7,8,38].…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [20] studied the impact of WDC on the HPYCS shear strength variations based on several tests. During this study, tests were conducted on the samples of HPYCS collected from a highway slope site borehole in Jackson, Mississippi.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…The effect of WDC in a controlled environment in the laboratory was investigated on the HPYCS samples with 76.2 mm diameter and 25.4 mm height, which were subjected to three, five, and seven repeats of the WDC and then tested for the void ratio, microstructure, volumetric deformation, and shear strength. Khan et al [20] reported the axial deformation of HPYCS under different WDCs. Furthermore, the fully-coupled flow and stability analysis with consideration of the soil unsaturated matric suction and moisture variation was also conducted.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…Black cotton soil is composed of fine-grained soil or decomposed rocks that show huge volume changes when subjected to variability in moisture content. Expansive soil shows swell-shrink behavior near the ground surface due to the land covered by expansive soil [6,7]. These soils occupy approximately 8.9×10 km 2 in India; approximately one-fifth of their surface area covers the states of Maharashtra, Gujarat, Uttar Pradesh, Madhya Pradesh, Rajasthan, Andhra Pradesh, Geotechnical Properties and Stability of Expansive Soil using Fly Ash Farhan KHAN et al http://wjst.wu.ac.th and Tamil Nadu [8,9].…”
Section: Expansive Soilmentioning
confidence: 99%